Development of an Acoustic Spot Data Communication System Using Multiple Parametric Array Loudspeakers. Issue 1 (27th September 2021) - Taniguchi, Yoshiaki; Morimoto, Kohei
Abstract : In this letter, we develop an acoustic spot data communication system using multiple parametric array loudspeakers, which are directional loudspeakers and can send audio in a specific direction. In our system, data are modulated and transmitted through multiple parametric array loudspeakers, and complete data reception is possible only at a specific spot. We implemented our system using low‐cost commercially available products and a self‐developed Java program, and we used frequency‐shift keying to modulate the acoustic data communication between the sender and receiver modules. Through comparative experimental evaluations, we show that data reception at a specific spot is possible using our system. © 2021 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.